Contrasting processing tomato cultivars unlink yield and pollen viability under heat stress. Issue 4 (17th July 2021) - Miller, Golan; Beery, Avital; Singh, Prashant Kumar; Wang, Fengde; Zelingher, Rotem; Motenko, Etel; Lieberman-Lazarovich, Michal
Abstract: Climate change is causing temperature increment in crop production areas worldwide, generating conditions of heat stress that negatively affect crop productivity. Tomato ( Solanum lycopersicum ), a major vegetable crop, is highly susceptible to conditions of heat stress. When tomato plants are exposed to ambient day/night temperatures that exceed 32 °C/20 °C, respectively, during the reproductive phase, fruit set and fruit weight are reduced, leading to a significant decrease in yield. Processing tomato cultivars are cultivated in open fields, where environmental conditions are not controlled; therefore, plants are exposed to multiple abiotic stresses, including heat stress. Nonetheless, information on stress response in processing tomatoes is very limited. Understanding the physiological response of modern processing tomato cultivars to heat stress may facilitate the development of thermotolerant cultivars. Here, we compared two tomato processing cultivars, H4107 and H9780, that we found to be constantly differing in yield performance. Using field and temperature-controlled greenhouse experiments, we show that the observed difference in yield is attributed to the occurrence of heat stress conditions. In addition, fruit set and seed production were significantly higher in the thermotolerant cultivar H4107, compared with H9780. Despite the general acceptance of pollen viability as a measure of thermotolerance, there was no difference in the percentage of viable pollen between H4107 and H9780 under either of the conditions tested. In addition to observations of similar pollen germination and bud abscission rates, our results suggest that processing tomato cultivars may present a particular case, in which pollen performance is not determining reproductive thermotolerance. Our results also demonstrate the value of combining controlled and uncontrolled experimental settings, in order to validate and identify heat stress-related responses, thus facilitating the development of thermotolerant processing tomato cultivars. Abstract : Our paper deals with the response of tomato plants to high temperatures. Tomato is an important crop, and tomato plants are very sensitive to high temperatures. Therefore, the increase in temperatures due to climate change poses a threat to tomato production. We found that a specific tomato cultivar is heat stress-tolerant, with better productivity under high temperatures. Usually, such tolerance is linked with pollen grains viability. Interestingly, in our case, pollen characteristics were eliminated as a causal factor for heat stress tolerance, meaning that other factors are involved. Follow-up studies are performed towards the development of heat-tolerant tomato.